Network security essentials : applications and standards - Stallings, William (Pearson Education Inc., 2003)
In this age of universal electronic connectivity, viruses and hackers, electronic eavesdropping, and electronic fraud, security is paramount. Network Security: Applications and Standards, Fourth Edition provides a practical survey of network security applications and standards, with an emphasis on applications that are widely used on the Internet and for corporate networks. An unparalleled support package for instructors and students ensures a successful teaching and learning experience.